Genetic variations in DNA repair gene NEIL1 associated with radiation pneumonitis risk in lung cancer patients. Issue 7 (9th June 2021) - Zheng, Yuming; Zheng, Leizhen; Yu, Jiahua; Jiang, Mawei; Zhang, Songfang; Cai, Xuwei; Zhu, Meiling
Abstract: Background: Radiation pneumonitis (RP) is a common side effect in lung cancer patients who received radiotherapy. Our previous study found genetic variations in DNA repair gene NEIL1 may be a predictor of RP in patients with esophageal cancer. So, we hypothesis genetic variations in NEIL1 gene could affect the risk of RP in lung cancer patients following radiotherapy. Methods: Genetic variations rs4462560 G>C and rs7402844 C>G in NEIL1 gene were genotyped in 174 lung cancer patients received radio(chemo)therapy. Luciferase assay, real‐time PCR and Western blot were used to access the effect of the variants on NEIL1 in HELF and HEF cell lines which were transfected with plasmids containing rs4462560 G>C and rs7402844 C>G. Results: Patients with rs4462560 CC genotype had a lower risk of RP grade ≥2 than GG genotype. Compared with the CC genotype, rs7402844 GG genotype was associated with an increased RP grade ≥2 risk. What is more, rs4462560 G decreased the relative luciferase activity of NEIL1 gene promoter compared with the negative control in vitro, while rs4462560 C can increase the relative luciferase activity. The mRNA and protein level of the NEIL1 gene in rs4462560 G were lower than rs4462560 C. Conclusions: Genetic variants of NEIL1 are associated with RP risk through regulation of NEIL1 expression and serve as independent biomarkers for prediction of RP in patients treated with thoracic radiotherapy. Abstract : We found genetic variants of NEIL1 are associated with RP risk in the study. These variants might exert their effect through regulation of NEIL1 expression and serve as independent biomarkers for prediction of RP in patients treated with thoracic radiotherapy.